POLITICS OF THE PTOLEMAIC DYNASTY (2016)
Hellenistic studies and Egyptology have concentrated on the spread and influence of Hellenism, on the one hand, and the value of ancient Egypt’s monument and artifacts, on the other hand. This study focuses on the politics that directed and helped sustain the successors of Alexander the Great on the throne of Egypt. Ptolemy 1 Soter. the instigator of the Ptolemaic dynasty, fought vehemently, gallantly and decisively to consolidate his authority and control over Egypt anjl her consequent spread. However, his successors played several politics; majorly that of assassination, for the enviable position of ^Pharaoh, unfortunately, to the detriment of the state. This study contends that besides the earliest Ptolemies, the other successors, having ignored the legacy of Ptolemy 1 Soter and the expansion of Egypt’s frontiers, fostered and nurtured this politics of assassination among others. It concludes with the argument that the contenders encouraged political retrogression to the nadir and therefore were not fit for the throne, for this politics of assassination among others reduced Egypt and hindered her from attaining the status of a much more formidable world power that would have been reckoned with during that period. The study is historical in nature but adopts the expository method. Studies that may interpret Egypt’s strong diplomatic relations with other ancient nations are recommended